Audit Quality and Investment Efficiency with Endogenous Analyst Information - Langberg, Nisan; Rothenberg, Naomi (The Accounting Review, 2023)
ABSTRACT We study audit quality and investment efficiency when an analyst’s information can curb overvaluation and auditors are subject to legal liability following audit failure. With the auditor’s damage payment based on price inflation after audit failure, the analyst’s information brings prices closer to fundamentals and provides a hedge to the auditor against legal liability risk. This weakens incentives for audit quality, and the analyst responds with more information production due to the penalty for mispricing. Consequently, in equilibrium, stricter legal liability leads to higher audit quality that reduces overinvestment but also less information production that increases underinvestment. Thus, stricter liability has a nonmonotonic effect on firm value; it increases the value of firms with a high valued growth option but reduces the value of firms with a low valued growth option. The results have implications for the optimal level of legal liability that maximizes the expected value of the firm. JEL Classifications: M41; M42; G14; G23; G32.